Impression Management Tactics and Performance Ratings: A Moderated-Mediation Framework - Bande Videla, Belén; Fernández-Ferrín, Pilar; Otero-Neira, Carmen; Varela-Aldás, José (Journal of Business to Business Marketing, 2017)
Purpose: The objective of this study is to contribute to the sales management literature by analyzing whether self-monitoring dimensions (the ability to adjust the presentation of one's self and the sensitivity to the expressive behaviors of others) play a moderating role in the use of impression managementsupervisor likingperformance rating nomological network.Methodology/approach: Empirical analysis is based on dyadic data from 122 industrial salespeople and their sales managers in 9 different industries. Structural equation modelling was used to analyze the psychometric proprieties of the measurement scales, and conditional process analysis was used to test the proposed hypotheses.Research implications: The results obtained indicate that the use of supervisor-focused impression management tactics is an indirect antecedent of a salesperson's performance rating through sales manager liking, but not the self-focused tactics. Results also show that a self-monitoring dimension i.e., the ability to adjust the presentation of one's self, moderates the impression managementsupervisor likingperformance rating chain. These results provide an increased understanding of the processes involved in sales managerssalespeople's interactions.Practical implications: The main implication for salespeople is that the use of impression management tactics to influence performance ratings only is effective when they use supervisor-focused tactics because attempts to influence via self-focused tactics will not have any effect. The most important implication for sales managers' is that not all impression management tactics are successfully executed and that the identification of combinations of impression management tactics and the levels of salespeople's self-monitoring can positively influence performance appraisals by generating evaluative biases. Given that evaluative biases can produce inequitable behaviors by sales managers in the task assignments and support provided to the salespeople, it is important that sales managers are aware of when they can occur (i.e., when salespeople with a moderate ability to adjust their self-presentation use supervisor-focused tactics).Originality/value/contribution of the article: This article contributes to the existing knowledge by two important means. First, this study proposes a model and presents an empirical test of constructs that mediate (i.e., supervisor liking) and moderate (i.e., self-monitoring dimensions) the use of impression management tacticssales manager likingperformance appraisal relation. This model responds to calls for studies that analyze how impression management tactics are related to performance appraisal and when the relation between the use of these tactics and performance rating occurs. Two, this study uses data from both salespeople and their sales managers, which minimizes any risk of common method variance bias.
Keywords: Impression management tactics; liking; performance rating; salespeople; self-monitoring; industrial marketing; business marketing; JCR; Scopus